Parental Guidance Advised: Associations Between Parental Television Limits and Health Behaviors Among Obese Children - Cheng, Jennifer K.; Koziol, Renata L.; Taveras, Elsie M. (Academic pediatrics, 2015)
To examine associations between parental limits on TV viewing and child health behaviors. We surveyed 816 parents of children 6 to 12 years of age who were participating in a primary care–based obesity intervention. The main exposures were parental limits placed on child TV viewing time and TV content. Outcomes included screen-related behaviors, sleep habits, eating routines, and physical activity. We performed bivariate and multivariable analyses to examine independent associations of parental TV viewing rules with our outcomes. In multivariable analyses adjusted for child age, sex, race/ethnicity; parental education and US-born status; income and primary language, children whose parents set limits on TV time were less likely to have a TV in their bedroom (odds ratio [OR] 0.45; 95% confidence interval [CI] 0.31, 0.64) or to fall asleep while watching TV (OR 0.47; 95% CI 0.34, 0.67). Children with parental limits spent fewer weekday hours watching TV (−0.38 hours/day; 95% CI −0.54, −0.21), playing video or computer games (−0.15 hours/day; 95% CI −0.25, −0.04), and using the Internet (−0.08 hours/day; 95% CI −0.15, −0.006). In addition, children with limits on TV time were less likely to eat breakfast (OR 0.73; 95% CI 0.53, 0.99) or dinner (OR 0.53; 95% CI 0.39, 0.73) with the TV on, and they slept longer during weeknights: 0.21 hours/day (95% CI 0.05, 0.36). Moreover, children whose parents set rules on TV programming content were also less likely to have a TV in their bedroom (OR 0.37; 95% CI 0.18, 0.79). The relationship between parental limits on TV viewing and obesogenic child behaviors deserves further investigation.